Said’s Orientalism and the Study of Christian Missions (Journal of Research for Christianity in China (JRCC), 2023)
Herb Swanson, “Said’s Orientalism and the Study of Christian Missions”, in International Bulletin of Missionary Research, volume 28, 2004, pp. 107-112.